Media – My ”Best” Teacher Curiosities and assumptions - TALAŞMAN-CHIOREAN, Claudia (Presa Universitară Clujeană, 2020)
The present book emerged from the desire to identify some effects that technology brings on the human psychic in the level of emotions, cognitions and behaviors, in specific social, cultural, professional contexts. Like any element of novelty, the technological explosion brings, besides the impetuous temptation, feelings of uncertainty, fear, concern about the side effects on the human psyche, derived from its intense use. In a way, history repeats itself. When the book was published for the general public, the humanity have the same anxiety: ʺWill not be the man adversely affected by the excessive consumption of books?ʺ In the romantic literature, prototype characters appeared who suffered from endless readings and intense study. The idea of learning was associated with the disease (possibly lung disease or some mental illness).